Odd-even graceful labeling of planar grid and prism graphs. Issue 4 (19th May 2021) - Basher, M.
Abstract: A graph G with p vertices and q edges is said to be odd-even graceful graph, if there exist an injective function f : V ( G ) → 1, 3, 5, … , 2 q + 1 such that induced function f * : E ( G ) → 2, 4, 6, … , 2 q defined by f *( uv ) =| f ( u ) − f ( v )| for every uv ∈ E ( G ) is a bijection. In this paper we proved that the planar grid and the prism admit odd-even graceful labeling.